Analisis Dan Perancangan Sistem Informasi Akuntansi Kas Rumah Sakit Menggunakan Metode SDLC Dan Framework BABOK Versi 3.0 - Ela Karenina; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to design a new cash accounting infornnation system at the hospitaI by analyzing the existing accounting system. The framework used as a reference for researchers is the framework BABOK version 3.0 and uses the SDLC method to make it easier to design the cash accounting information system. Analysis of the hospital cash accounting information system is carried out by identifying cash problems that occur, identifying decision points, identifying key personnel related to cash either directly or indirectly. In designing a cash accounting information system at hospital in Cikalongwetan, the authors designed the right procedures so that the hospital could maximize cash control, both for cash receipts and cash disbursements. Therefore, the authors make recommendations for designing a cash accounting information system in RSUD Cikalongwetan according to user needs, so that it can simplify the works.